The Conservation of Osingnese Traditional Home Garden Agroforestry in Banyuwangi, East Java, Indonesia - Luchman Hakim; Nila Ratih Pamungkas; Karuniawan Puji Wicaksono; Soemarno Soemarno (AGRIVITA, Journal of Agricultural Science, 2018)
Local culture and traditions have been considered as an important factor in influencing plant species diversity and composition of home garden, but their interactive effect have not yet been investigated. This research aimed to describe the plant species diversity in traditional home gardens, identify the species with important value based on ethnobotanical indices, and describe the perception of local people towards agroforestry conservation in Osingnese Villages in Banyuwangi. Data acquisition was performed at Kopen Dukuh, Buluhsari-Kopen Cungking, and Kemiren Villages. Floristic survey was implemented at 75 home gardens. An interview was implemented for each owner. Results showed that Osingnese home gardens consist of numerous plant species. Kopen Dukuh and Buluhsari-Kopen Cungking showed a complex structure which could be considered as a complex agroforestry. Cocos nucifera, Coffea canephora, Coffea liberica, Garcinia mangostana, and Durio zibethinus were the important species in complex agroforestry. Those species composition indicated that home gardens are able to conserve native plants of Malaysian regions, particularly Indonesian flora. Agroforestry knowledge was derived from the older generations and implemented in gardening practices. They also argued that recent agroforestry is an adaptation mechanism of land management. The government did not contribute to educate and empower local people about agroforestry practices.